Effects of Timber Density on Northern Bobwhite Autumn Abundance - Ian T. Little; Shane D. Wellendorf; William E. Palmer; John P. Carroll (National Quail Symposium Proceedings, 2017)
Mature pine (Pinus spp.) ecosystems maintained with frequent prescribed fire are the primary habitat of northern bobwhites (Colinus virginianus) in the Red Hills region of northern Florida and southern Georgia. Timber volume is thought to be negatively related to bobwhite abundance; however, this relationship has not been quantified. We related mean basal area of mature trees (>15cm dbh) to autumn covey call count indices at 23 locations on 6 study areas with varying timber volume, but similar bobwhite management practices, 2002 - 2004. Bobwhite abundance was inversely related to timber volume (r = -0.61, P = 0.002). Adjusted covey counts averaged 11.3 coveys below, and 6.4 coveys above, 9.2 m2/ha (40 ft^2/ac) of basal area (F1,21 = 19.4, P < 0.001). Where maintaining high densities of bobwhites is a priority, we recommend pine basal areas be < 10 m^2/ha. However, our data also suggested that bobwhites can be maintained at a bobwhite/0.4 ha at basal areas up to 14 m2/ha assuming sound management is applied.
Keywords: abundance; autumn; basal area; Colinus virginianus; northern bobwhite; quail; timber